(untitled) (Research, Society and Development, 2020)
Ankyloglossia is a congenital abnormality, more linked to the male sex and with a prevalence of 4 to 10% in live newborns. This presents as a short or very anterior lingual frenulum; causing difficulty, limitation and impossibility for the tongue to fulfill its role within the stomatognathic system. The treatment for this condition is frenectomy, this procedure is usually performed under general anesthesia in children of an early age, therefore, the purpose of this paper is to present a protocol for early frenectomy care with topical anesthesia and / or local treatment for the treatment of ankyloglossia in children under 5 years of age since the early diagnosis of ankyloglossia can result in a quick, effective solution, with minimization of its effects on the child and in some cases with a shorter and easier postoperative period. By the way, we present two cases where in the first case it is a 2-month-old girl and the second case a 4-case boy, in the first case a frenotomy was performed and in the second case a frenectomy.